A randomised controlled trial comparing rehabilitation against standard therapy in multiple sclerosis patients receiving intravenous steroid treatment. Issue 9 (21st August 2003) - Craig, J; Young, C A; Ennis, M; Baker, G; Boggild, M
Abstract : Background: There is evidence to support both the use of intravenous methylprednisolone (IVMP) in multiple sclerosis (MS) relapse and physiotherapy in the management of MS, but no studies have investigated the combination of steroids and rehabilitation together. Objectives: To evaluate the benefits of IVMP with planned, comprehensive multidisciplinary team (MDT) care compared to IVMP with standard care. Methods: In this randomised controlled trial, patients confirmed to have had a definite MS relapse severe enough to warrant IVMP (1 g daily for three days) were randomised to two groups. The control group was managed according to the standard ward routine; the treatment group received planned coordinated multidisciplinary team assessment and treatment. Baseline assessments, including demographics and Expanded Disability Status Scale (EDSS) were carried out on both groups. The primary outcome measures were Guy's Neurological Disability Scale (GNDS), and Amended Motor Club Assessment (AMCA). The secondary measures were the Barthel Index (BI), Human Activity Profile (HAP), and Short Form Item 36 Health Survey (SF-36). All measures have published data on reliability and validity. Measures were administered at one and three months. Results: Forty subjects, including 27 females, completed data collection. There were no significant differences between the two groups at baseline. Results showed statistically significant differences in GNDS (p = 0.03), AMCA (p = 0.03), HAPM (p < 0.01), HAPA (p = 0.02), and BI (p = 0.02) at three months in favour of planned MDT care. Conclusion: This study indicates that combining steroids with planned MDT care is superior to administering them in a standard neurology or day ward setting. Further research is necessary in order to confirm this finding.